Learning to Philosophise and to Argue, A thinking Skills Programme for Children (Analytic Teaching, 1996)
Introduction:  My purpose in this paper is to offer an account of a thinking skills programme which focuses both on the teaching of philosophy and of argument. The programme is based on three assumptions: (1) teaching critical thinking is essential to any adequate notion of 'education for citizenship'; (2) such teaching acts as a counter to certain kinds of indoctrination; (3) young children are willing and able to engage in philosophical discussion and debate. The central goal of my programme, 'Teaching Philosophical Thinking and Argument', is to promote the development of thinking, reasoning and argument skills through the discussion of philosophical issues. In what follows, I shall examine the theoretical underpinnings of the programme and how it is conducted, in practice, in the classroom.